Responsible Research Practice Revisiting Transformative Paradigm in Social Research - Romm, Norma RA (Springer International Publishing, 2018)
This book explores ways in which creative research practice can be explicitly and mindfully geared to make a difference to the quality of social and ecological existence. It offers a range of examples of how different research methods can be employed (and re-tuned) with this intention. The book suggests that what Romm names "active" research involves using the research space responsibly to open up new avenues for thinking and acting on the part of those involved in the inquiry and wider stakeholders. The book includes a discussion of a range of epistemological, ontological, methodological and axiological positions (or paradigms) that can be embraced by inquirers implicitly or explicitly. It details the contours of an epistemology where knowing is recognized to be grounded in social relations, as a matter of ethics. While focusing on discussing the "transformative paradigm" and attendant view of research ethics, it considers to what extent the borders between paradigms can be treated as being permeable in creative and active inquiries. Apart from considering options for enhancing responsible research practice during the process of inquiry (and reconsidering mixed-research designs) the book also considers options for responsible theorizing that is inspirational for pursuing goals of social and ecological justice. .